Phytotoxicity Of Zinc-Nanoparticles And Its Influence On Stevioside Production In Stevia Rebaudiana Bertoni (Applied Biological Research, 2015)
The present study was aimed to assess the effect of zinc-nanoparticles  (Zn-NPs) on the growth and development of stevia (Stevia rebaudiana Bertoni) plant and to decipher the impact of Zn-NPs on secondary  metabolite production. In present study, Zn-NP (< 100 nm) @ 50, 10200, 400 and 1000 mg L-1 concentration was tested. The nodal explants of stevia were cultured in vitro on MS medium where normal source of  Zn was replaced with different concentrations of Zn-NPs. The Zn-NPs  showed potential toxicity to stevia plant that was reflected from both  morphological data as well as from the production of reactive oxygen  species (ROS) scavenging enzymes under different treatment conditions.  The 200 mg L-1 concentration of Zn-NP showed lower toxicity symptoms.  The phytotoxicity severity increased at concentration of 400 mg L-1 and  above with highest toxicity at 1000 mg L-1 concentration. The production  of stevioside was significantly reduced when exposed to Zn-NP in a  concentration depended manner. The study showed concentration  dependent phytotoxic effect of Zn-NP on the physiology and stevioside  production in stevia.
Keywords: Phytotoxicity; ROS enzymes; stevia; Zn-nanoparticle; stevioside